MANFAAT KAGHATI ROO KOLOPE BAGI MASYARAKAT MUNA SEBELUM ISLAM - Wa Ode Sifatu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This article aims at revealing the benefits of Kaghati roo kolope for the Muna community before Islam. The underlying theory is Clifford Geertz's (1959) thinking about brokers, with ethnographic methods. Results: Four Muna community classification: Kaomu, Walaka, Anangkolaki / Fitubhenkauno, and Wawono Liwu / Wawono Wite. You can be a king if Kaghati roo kolope can air seven days and seven nights. Such a model of the election of kings does not have the potential for conflict between groups because each contestant and his supporters surrender themselves to nature. In conclusion, the broker in Javanese society to his god is Kiyai, while the broker in Muna society before Islam is Kaghati roo kolope. Muna people should be able to maintain the local wisdom of Kaghati roo kolope. Keywords: Kaghati roo kolope, the election of Muna kings before Islam